Current perspectives in kidney diseases - La Manna, Gaetano 1962-; Ronco, Claudio 1951- (Contributions to nephrology / series editor Claudio Ronco, 2017)
After years of stagnation, much has been happening in the diagnosis and treatment of kidney diseases. This book contains a comprehensive review of the main developments in AKI, CKD, hemodialysis and kidney transplantation. The section on AKI deals with the key innovations in extracorporeal technologies. The section on nephrology and CKD concentrates on mineral metabolism alterations, restenosis in hemodialytic fistulas, mycophenolate mofetil as an alternative treatment for IgA nephropathy, and the genetics and progression of autosomal dominant polycystic kidney disease. The part on hemodialysis includes contributions on expanded hemodialysis, potassium profiling and home hemodialysis. Chapters on the treatment of acute antibody-mediated rejection after transplantation, pathogenesis and therapy of chronic allograft injury, and non-invasive surrogate biomarkers of acute rejection round out the subjects covered. Due to the wide variety of topics included in each section, this book is not only of interest to nephrologists, but also to professionals from related fields.